Upaya Meningkatkan Kemampuan Komunikasi Siswa Dengan Penerapan Strategi Pembelajaran Think Talk Write Pada Siswa Kelas VIII SMP Negeri 3 Medan - Zulmawati Zulmawati; Risma Hartati (Journal on Education, 2024)
This research aims to improve students' communication skills and determine efforts that can be made to overcome communication difficulties experienced by students in social science subjects in class VIII SMP Negeri 3 Medan for the 2023/2024 academic year. This type of research is Classroom Action Research (PTK). The subjects in this research were 27 students in class VIII-B of SMP Negeri 3 Medan. The object of this research is improving students' communication skills by implementing the Think-talk-write learning strategy. The instruments used in this research were observation and tests. This research consisted of 2 cycles and at the end of each cycle a mathematical communication skills test was given. Before being given, the test is first validated by the validator. The results of research in cycle I showed that students who understood aspects of writing reached 77.78% (medium category), students who were able to understand aspects of representation reached 59.26% (poor category), and classical completion in cycle I reached 74.07% (category Enough). The results of research in cycle II showed that students who understood aspects of writing reached 88.89% (good category), and students who were able to understand aspects of representation reached 85.19% (good category), and classical completion in cycle II reached 88.89% ( good category).. Based on the description above, it can be concluded that using the Think-talk-write learning strategy can improve students' communication skills in social studies subjects in class VIII-B of SMP Negeri 3 Medan for the 2023/2024 academic year.